Cotton Leaf Feeding on Cotton Fiber Quality Indicators - Tukhtashev Farrukhjan Esonali ugli (Web of Journals Publishing, 2023)
In order to develop the period and norms of cotton foliar feeding, Uni-agro liquid nitrogen fertilizer was applied to the growth, development and productivity of cotton in the soil-soil climate of Fergana region. as well as to study the effect of cotton fiber on the quality indicators, as well as to recommend for production.